ARS INVENTIO IN THE B.A.C.H. SYMPHONY FOR ORGAN SOLO BY SIGISMUND TODUŢĂ - Mirela MERCEAN-ŢÂRC (Studia Universitatis Babeş-Bolyai. Musica)
The paper intends to outline the role of this symphony in the cultural landscape of Romanian and universal Modernity by referring it to the Neo-Baroque trend characteristic for this Transylvania born composer. S. Toduţă, the first Doctor in Musicology in Romania, the creator of a valuable composition school in our cultural space, is celebrated on the anniversary of 100 years from his birth.